Kemampuan Zeolit dan Batu Apung Sebagai Media Filter dan Adsorpsi untuk Menyisihkan Salinitas, TDS, Konduktivitas dan TSS Pada Air Payau Menjadi Air Bersih - Qoriatul Khoiriyah; Yayok Suryo Purnomo (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
Brackish water has a characteristic cloudy yellow colour and a higher pH than fresh water. Not a few residents complain about the condition of the water, which feels brackish to salty, their skin feels sticky after bathing, this is due to the salinity in the water (Ismawan, Sanjoto, & Setyaningsih, 2016). The salinity in brackish water is 0.5-30 ppt, TDS is 1500-6000 ppm. The filtration process uses zeolite and pumice as adsorption media. The sample water is passed through the filtration media from bottom to top and collected in useful as adsorbent because of zeolit and pumice have pores that can bind molecules in water. From the research results, the average value of zeolite media was able to remove salinity of 28.84%, TDS 28.06%, conductivity 28.14% and TSS 92.20%. And pumice stone media is able to remove salinity of 28.57%, TDS 27.81%, conductivity 27.88% and TSS 91.20%. The adsorption capacity value was calculated using the Thomas method and the result obtained for the zeolitic media was 0.059 mg adsorbate/mg adsorbent, while for the pumice stone media it was 0.026 mg adsorbate/mg adsorbent. It can therefore be said that the zeolite media has a greater capacity and removal capacity than pumice.